Randomised, Double-Blind, Placebo-Controlled Study of Iguratimod in the Treatment of Active Spondyloarthritis - Li, Yan; Li, Kunpeng; Zhao, Zheng; Wang, Yanyan; Jin, Jingyu; Guo, Junhua; Zhang, Jie; Zhang, Jianglin; Zhu, Jian; Huang, Feng (Frontiers in Medicine, 2021)
Abstract Background and purpose: The effect of Iguratimod in the treatment of rheumatoid arthritis was confirmed in past studies. In terms of the mechanism of the effect and clinical application experience, Iguratimod has a potential value in the treatment of spondyloarthritis (SpA). This study evaluated the efficacy and safety of Iguratimod on active SpA. Methods: Subjects with active SpA were enrolled and randomly divided into two groups at a ratio of 1:2 (placebo vs. Iguratimod). On the basis of non-steroidal anti-inflammatory drugs, combined treatment with Iguratimod or placebo, followed by follow-up every 4 weeks for 24 weeks. The primary efficacy endpoint was to evaluate the alleviation rate of ASAS20; the important improvement of ASDAS and the efficacy of spinal mobility, physical function and quality of life at the 24th week. Results: A total of 48 cases in the Iguratimod group and 25 cases in the placebo group were included in the final analysis. On the 24th week, the percentage of responders to ASAS20 (80% vs. 44%) and ASAS40 (56% vs. 20%) treated with Iguratimod were significantly higher than that in the placebo group (P < 0.05). Twelve cases had gastrointestinal discomfort, of which eight were in the Iguratimod group (16.7%, one case withdrew from the study due to diarrhoea) and four were in the placebo group (16.0%). No significant difference was found between the two groups (P < 0.05). Three cases of elevated transaminase were observed in the Iguratimod group and none in the placebo group, with no significant difference (P < 0.05). Conclusion: Iguratimod could significantly reduce the symptoms and signs of patients with active SpA. It could improve the physical function and quality of life of these patients and the overall safety and tolerance are good.